Mapping of Human Resource Characteristics of MSME in Pandeglang District, Pandeglang Regency, Banten Province - Renny Husniati; Alnisa Min Fadilah (Management and Leadership Study Programme, 2020)
Human resources (HR) is one of the most important factors that cannot be separated from an organization, both an institution and a company. HR is also a key that determines the development of the company. Errors in the selection of human resources will adversely affect the achievement of organizational goals. Human resources must be empowered with the management and development or also called human resource management. This study aims to gather information regarding HR at MSMEs in Pandeglang Regency and how these characteristics can influence the development of the business being run. From the results of the mapping of HR characteristics, it is expected to be of use to the relevant department, by obtaining information on the potential of MSME in Pandeglang Regency by identifying and field surveys. Looking at the potential of Small Medium Enterprise (SME), a coaching program can be formulated so that an independent SME will be formed that can be developed to raise local excellence. For SME, it is an opportunity to develop their business through assistance and guidance in accordance with management needs. This mapping uses a survey method that is digging data through the distribution of questionnaires including data on HR characteristics and knowledge, skills and attitudes in managing a business. From the results of the study, it can be seen the average score of the three indicators, that is knowledge of 2.95, skills of 2.97 and attitudes of 3.05. This means that in managing a running business is good enough.